In Defense of Indirect Communication. Issue 2 (17th February 2016) - Szabó, Zoltán Gendler
Abstract: In Imagination and Convention, Ernest Lepore and Matthew Stone claim that there are no conversational implicatures. They argue that the scope of the conventional is wider and the scope of communication narrower than followers (or even critics) of Grice tend to assume, and so, there is simply no room for the sort of indirect communication based on reasoning about intentions conversational implicatures are supposed to exemplify. This way they seek to rehabilitate the old Lockean model of linguistic communication. I argue that while the book is successful in undermining a number of Gricean analyses, the core cases of conversational implicature resist recasting in terms of disambiguation or creative interpretation. Granting that linguistic communication relies more heavily on conventions and that interpretation is more frequently open-ended than it is usually thought cannot save the Lockean model.